Marketing Innovation, Employee Competence, Customer Orientation, and Product Quality on Market Performance and Organizational Reputation in Indonesian Multinational Companies - Iswanto Iswanto; Ni Desak Made Santi Diwyarthi; I Wayan Adi Pratama (Fakultas Ekonomi Universitas Garut, 2025)
This study examines the effects of marketing innovation, employee competence, customer orientation, and product quality on market performance and organizational reputation among Indonesian multinational companies. In an increasingly competitive global business environment, these factors are recognized as key strategic resources that determine both operational success and long-term corporate image. Using a quantitative research design, data were collected from 150 respondents via a Likert scale (1–5) and analyzed through Structural Equation Modeling–Partial Least Squares (SEM-PLS 3). The results show that all four independent variables—marketing innovation, employee competence, customer orientation, and product quality—positively and significantly influence market performance. Furthermore, these variables also exert significant positive effects on organizational reputation, both directly and indirectly through market performance. Among them, product quality exhibits the strongest effect on market performance, while market performance itself significantly enhances organizational reputation. The findings suggest that the synergy between innovative marketing, competent human resources, customer focus, and superior product quality contributes to improved competitiveness, customer satisfaction, and reputation building. This study provides valuable theoretical and managerial implications for multinational corporations operating in Indonesia, emphasizing the importance of continuous investment in innovation, employee capability development, customer relationship management, and product quality assurance to sustain high performance and a positive organizational reputation in both global and local markets.